2005
DOI: 10.1007/s00421-005-1375-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concurrent inspiratory and expiratory muscle training on respiratory and exercise performance in competitive swimmers

Abstract: The efficiency of the respiratory system presents significant limitations on the body's ability to perform exercise due to the effects of the increased work of breathing, respiratory muscle fatigue, and dyspnoea. Respiratory muscle training is an intervention that may be able to address these limitations, but the impact of respiratory muscle training on exercise performance remains controversial. Therefore, in this study we evaluated the effects of a 12-week (10 sessions week(-1)) concurrent inspiratory and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 56 publications
8
66
3
2
Order By: Relevance
“…The present study is in agreement with prior studies (Clanton et al 1987;Wells et al 2005) showing inspiratory muscle strength increases as a result of competitive swim training. In addition, the work per breath derived from the SMIP power curve (joules) increased following the 12 week swim conditioning period.…”
Section: Respiratory Muscle Functionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study is in agreement with prior studies (Clanton et al 1987;Wells et al 2005) showing inspiratory muscle strength increases as a result of competitive swim training. In addition, the work per breath derived from the SMIP power curve (joules) increased following the 12 week swim conditioning period.…”
Section: Respiratory Muscle Functionsupporting
confidence: 94%
“…These results conflict with those reported for subjects engaged in IMT but without swim training. Similarly, Wells et al (Wells et al 2005) recently demonstrated in adolescent competitive swimmers that 12 weeks of swim training was as effective as swim training plus pressure-threshold respiratory muscle training in eliciting improvements in respiratory muscle strength.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The anomalous respiratory characteristics of competitive swimmers have been suggested to be due to the extraordinarily advanced respiratory muscle work [35]. All swimmers, not only elite individuals, appear to be a special group of athletes with lung function greater than predicted and better than in other endurance athletes [18,36].…”
Section: Discussionmentioning
confidence: 99%
“…S u b s e q u e n t s t u d i e s h a v e s i n c e documented the efficacy of IMT [6][7][8][9][10][11] , and the American Thoracic Society and European Respiratory Society 2) issued a statement that, "IMT could be considered as adjunctive therapy in pulmonary rehabilitation, primarily with suspected or proven respiratory muscle weakness." Studies have shown that expiratory muscle training (EMT) increases maximal expiratory muscle pressure (PE max ), improves pulmonary function, ventilation function and exercise capability and alleviates respiratory distress caused by inspiratory load, activities of daily living or exercise in patients with COPD 12,13) , healthy individuals 10,[14][15][16][17][18][19] , multiple sclerosis (MS) patients [20][21][22] , myasthenia gravis (MG) patients 23) , neuromuscular disease (NMD) patients 24,25) , patients with tetraplegia caused by spinal cord injury 26,27) and Parkinson's disease patients 28,29) . However, some studies have found that: EMT does not increase PE max 30) ; EMT only i m p r o v e s P E m a x , w i t h n o e f f e c t o n o t h e r parameters 31,32) ; and EMT increases PE max , but has no marked impact on other parameters or sufficient evidence is lacking [33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%